Influence of the Market Supply of Construction Land on the Misallocation of Labor Resources: Empirical Evidence from China - Changjun Jiang; Jintao Li (Land, 2022)
Economic development often leads to the misallocation of labor resources, so reforming the way land is allocated is important for developing a strategy to address the insufficient supply and oversupply of labor in China. This paper uses panel regression analysis to quantitatively measure the effect of the market supply of construction land (MSCL) on labor resources misallocation (LMIS). The results show that LMIS decreased year-by-year during the study period. The development of the MSCL can effectively reduce LMIS. The negative effect of the MSCL in the central region is greater than that in the eastern region, and the negative effect in the western region is the smallest. There is a single-threshold effect on the impact of the MSCL on LMIS. Specifically, when the MSCL is less than 18,045 hectares, the impact effect is −0.324, and when the MSCL is higher than 18,045 hectares, the effect is not significant. Moreover, the impact of the MSCL on LMIS has a spatial spillover effect, which is greater than the direct effect. Labor resources tend to migrate to economically developed areas, not just adjacent areas. These conclusions are of great significance for reducing LMIS from the perspective of land system reform in China.